?NORTH CAROLINA DESIGN - 11 ANALYSIS FOR ESTIMATING GENETIC PARAMETERS IN COTTON (GOSSYPIUM HIRSUTUM L.) - Baloch, Mohammed Jurial (Biological Sciences - PJSIR, 2003)
Genetic information is very important in formulating effective plant breeding programmes. North Carolina Design - 11 analysis was used to determine general combining ability (GCA), specific combining ability (SCA) and additive and dominant genetic variances for six quantitative traits in Upland cotton. In per se hybrid performance, parents CRIS - 241 and CRIS - 121 when crossed with other parents formed higher bolls per plant and produced more yield and lint %. It is usually predicted that per se hybrid performance is also reflected to SCA of the parents. This assumption did not always hold true, however, parents CRIS - 241 and CRIS - 121 that were good in per se hybrids and in GCA also formed good SCA when crossed with CRIS - 134 and CIM - 448, respectively. These results thus suggested that CRIS - 241 and CRIS - 121 are better parents simultaneously for per se hybrids, GCA and SCA. Genetic variation due to males (GCA), females (GCA) and males x females (SCA) were significant for all the traits except females for boll weight which indicated that both additive and dominant genes were important for characters under study. Similar to genetic variation due to GCA and SCA, estimates of additive and dominant genetic variances were also substantial suggesting that these characters can be improved either by hybridization and selection or suitable for hybrid cotton. The proportional contribution of GCA and SCA combining ability variances to total genetic variance further revealed that about equal proportions of additive and dominant genetic variances were available for all the traits except boll weight where additive variance was much higher than dominant variance.